Synthesis of Sparse Planar Arrays Using Matrix Mapping and Differential Evolution - Liu, Heng; Zhao, Hongwei; Li, Weimei; Liu, Bo (IEEE antennas and wireless propagation letters, 2016)
This letter proposes a differential evolution (DE) with matrix mapping for sparse rectangular planar array synthesis technique with multiple constraints. The multiple constraints include the number of elements, the planar array aperture, and the minimum spacing of adjacent elements. By introducing a novel matrix mapping between the element spacing and the variables of DE, the strong constrained optimization problem is transformed to a nonconstrained problem with only lower and upper limits, and the infeasible solutions are naturally avoided during the optimization process. The simulation results show the high efficiency and the robustness of the proposed method and indicate that our method can achieve better results than existing methods.